Updated diagnoses for the Indian species of Streptocephalus (Crustacea: Branchiopoda: Anostraca) - Velu, Chinavenmeni S.; Munuswamy, Natesan (Zootaxa, 2005)
The taxonomic status of the Indian Streptocephalus (S. dichotomus, S. echinus, S. longimanus S. spinifer, and S. simplex) is reevaluated and updated with additional information on various features such as penes, cercopods, and cysts. Surface ornamentation of the cysts is species-specific and therefore useful in identification.